An analysis of published cases of cutting balloon use in spontaneous coronary artery dissection - Maričić, Bojan; Perišić, Zoran; Kostić, Tomislav; Božinović, Nenad; Petrović, Milovan; Čanković, Milenko; Mehmedbegović, Zlatko; Juričić, Stefan; Vasilev, Vladimir; Dakić, Sonja; Perišić, Jelena; Milošević, Jelena; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction SCAD involves a sudden tear or separation within the layers of the coronary artery wall, resulting in blood flow obstruction and subsequent myocardial ischemia. Materials and methods A comprehensive literature search was conducted to identify relevant published cases of cutting balloon use in patients diagnosed with spontaneous coronary artery dissection. Electronic databases including PubMed, MEDLINE, Embase, Cochrane Library and Google Scholar were systematically searched from inception until the present using terms “cutting balloon,” “SCAD,” “acute coronary syndrome,” “intramural hematoma,” and “angioplasty.” Results A total of 32 published cases of cutting balloon use in spontaneous coronary artery dissection were analyzed in this study. The majority of the patients included in the analysis were female without prior history of cardiovascular disease. The median age of the SCAD population was approximately 46 years. The most frequently affected artery in SCAD cases was the Left Anterior Descending artery. Intravascular ultrasound was utilized more frequently than other modalities of adjunctive imaging techniques. The most frequent complication was the distal propagation of hematoma. Despite the successful dilation achieved with the cutting balloon, in some cases stenting was required to provide additional support. Conclusion The results of this analysis demonstrate that cutting balloon use in SCAD cases yields favorable outcomes.